The effect of Vitamin C supply in commercial feed on the growth and survival of tawes fish fry (Barbonymus gonionotus) - Ica Maria Simamora; Agus Putra A. Samad; Siti Komariyah (Acta Aquatica: Aquatic Sciences Journal, 2026)
The silver barb (Barbonymus gonionotus) is a freshwater fish found abundantly in Indonesian waters and belongs to the Cyprinidae family. This study aimed to determine the effect of vitamin C supplementation in commercial feed on the growth and survival of silver barb (Barbonymus gonionotus) fry. The research design used was a completely randomized design (CRD) with four replication treatments P1 = (Feed without additional vitamin C (control), P2 = Feed with additional vitamin C 100 mg / kg, P3 = Feed with additional vitamin C 150 mg / kg, P4 = Feed with additional vitamin C 200 mg / kg. The test fish used were 120 tawes fish measuring 4-6 cm. The research was conducted at the UPTD Pinang Mancung Fish Seed Center, Tebing Tinggi City for 40 days. Feeding the fish was carried out 3 times a day. The parameters measured included the main parameters in the form of absolute weight growth, absolute length growth, specific growth rate (LPS), feed conversion ratio and survival. Supporting parameters in the form of air quality parameters, namely temperature, pH, dissolved oxygen (DO) and ammonia. had a significant effect (P> 0.05) on the survival of tawes fish. The treatment that provided the best growth in this study was treatment P4 (200mg vitamin C / kg (feed). Keywords: Growth; Feed; Tawes Fish; Vitamin C